Pathogenicity of mycoplasmas isolated from goats - SINGH, M P; PRASAD, R L (The Indian Journal of Animal Sciences, 2013)
Mycoplasma mycoides subsp. mycoides, M. agalactiae and M. arginini isolated from natural cases of pneumonia were tested for their pathogenicity in mice and goats. M. mycaides subsp. mycaides and M. agalactiae were quite pathogenic as shown by septicaemia lasting for more than 72 hr in mice. M. arginini caused septicaemia in mice lasting from 24 to 48 hr. M. mycaides subsp. mycoides amI M. agalactiae were pathogenic forkids but the former was more pathogenic than the latter as shown by slightly less incubation period, higher febrile peak, higher mortality and more extensive and pneumonic lesions in the lungs.